The autumn kingdom. Volume one, Through the blight - Bunn, Cullen (Oni-Lion Forge Publishing Group, LLC, 2025)
"Fantasy novelist Andrew Kier takes his family on an idyllic vacation to the edge of a lush Swedish forest, where he hopes to finish writing his latest book in The Wraithbound Queen series. After his young daughters, Sommer and Winter, venture into the woods and find a clearing of statues nearby--featuring trolls, goblins, and a warrior queen missing her swordhand and weapon--a horde of fearsome fae creatures smash into their cabin and kidnap Andrew and his wife, Melissa. Sommer and Winter evade capture and flee into the forest, where they stumble upon a giant sword that mysteriously grants them the power to fight the monsters who stole their parents. As the girls slice their way to answers, centuries of horror and conflict are revealed, and they descend into the Autumn Kingdom to save their family--and their sisterly bond--if they're not too late"--